2004
DOI: 10.1038/sj.eye.6701648
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of the management of silicone oil-induced raised intraocular pressure by diode laser cycloablation

Abstract: Aims/background To analyse the effectiveness and safety of cyclodiode treatment in eyes with silicone oil-related raised intraocular pressure (IOP) and to correlate the results with clinical features of treated eyes. Methods Retrospective review of case notes of all eyes that underwent cyclodiode treatment following injection of silicone oil at Moorfields Eye Hospital between April 1993 and January 2003 and were followed up for at least 1 year. Results In all, 38 patients were followed up for between 13 and 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
18
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 19 publications
5
18
1
Order By: Relevance
“…Its success rate varies from 66% to 86%. 11,12,17 According to our best knowledge, this is the largest study that evaluates the results of TDCP in eyes with medically uncontrolled IOP secondary to emulsification of SiO. Our present study suggests a long-term success (IOP<21 mmHg) rate of 84% at 12 months and 90% at final follow-up visit of up to 41 months.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…Its success rate varies from 66% to 86%. 11,12,17 According to our best knowledge, this is the largest study that evaluates the results of TDCP in eyes with medically uncontrolled IOP secondary to emulsification of SiO. Our present study suggests a long-term success (IOP<21 mmHg) rate of 84% at 12 months and 90% at final follow-up visit of up to 41 months.…”
Section: Discussionsupporting
confidence: 49%
“…The secondary glaucoma following the use of SiO with retinal surgery may be caused by migration of emulsified oil to the anterior chamber, synechial angle closure, rubeosis iridis, pupillary block, and inflammation, or a combination of these. 17,18 However, prophylactic surgical inferior iridectomy reduces the risk of pupillary block glaucoma in aphakic eyes. The migration of emulsified oil to the anterior chamber and into the trabecular meshwork may mechanically obstruct the trabecular meshwork or it may cause inflammation of the trabecular meshwork, leading to decreased outflow facility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Successful IOP control has been reported in 66–82% of patients at 1 year [9092]. However, Sivagnanavel et al [93] reported a 56% treatment failure rate despite the use of higher mean laser energies and a higher retreatment rate.…”
Section: Glaucoma After Silicone Oil Injectionmentioning
confidence: 99%
“…[13] A few reports have shown diode laser trans-scleral cyclophotocoagulation (TSCPC) as an effective tool in controlling IOP in SO-induced glaucoma. [45] We intended to look for short-term and long-term IOP control following diode laser TSCPC in Chinese eyes.…”
mentioning
confidence: 99%